New chimeric HDAC inhibitors for the treatment of colorectal cancer. Issue 2 (28th November 2022) - Bär, Sofia I.; Pradhan, Rohan; Biersack, Bernhard; Nitzsche, Bianca; Höpfner, Michael; Schobert, Rainer
Abstract: Colorectal cancer is the third most common cause of cancer‐associated deaths due to a high recurrence rate and an increasing occurrence of resistance to established therapies. This highlights the importance of developing new chemotherapeutic agents. The current study focuses on cancer‐specific targets such as apoptosis‐inhibiting survivin, which distinguishes cancer cells from healthy tissue. A combination of pharmacophores of established anticancer agents to afford chimeric pleiotropic chemotherapeutic agents was tested on this cancer entity. We analysed the effects of the dual mode anticancer agents, animthioxam, brimbam, troxbam, and troxham, as well as their structural congeners suberoylanilide hydroxamic acid and combretastatin A‐4 on human cancer cell lines. Their cytotoxicity was determined using the MTT assay, further techniques for detecting apoptotic events, cell cycle analyses, clonogenic and wound healing assays, immunostaining, histone deacetylase (HDAC) activity measurements, and Western blot analysis for the detection of survivin expression in HCT116 colon cancer cells. Molecular docking studies were conducted to assess potential molecular targets of the test compounds. The test compounds were found selectively cytotoxic toward cancer cells by inducing apoptosis. The metastatic potential was effectively reduced by disruption of the microtubular cytoskeleton. The test compounds were also proven to be general HDAC inhibitors and to lead to reduced survivin expression. Abstract : Chimeric conjugates modeled on the drugs combretastatin A‐4 ( Z ‐stilbene) and suberoylanilide hydroxamic acid (hydroxamate) showed a pleiotropic mechanism of anticancer action, characterized by histone deacetylase inhibition, antimetastatic effects, induction of apoptosis, and downregulation of the cancer‐specific protein survivin. Troxbam, in particular, displayed outstanding efficacy against several human cancer cell lines.